Low-temperature orientational ordering and possible domain structures in C60 fullerite - Loktev, Vadim M.; Khalack, Julia N.; Pogorelov, Yuri G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
Based on a simple model for the ordering of hexagons on a square planar lattice, an attempt has been made to consider the possible structure of C60 fullerite in its low-temperature phase. It is shown that hexagons, imitating fullerenes oriented along the C3 axes of the sc lattice, can be ordered into an ideal structure with four nonequivalent molecules in the unit cell. Then the energy degeneracy for the rotationof each hexagon by p/3 around its C3 axis leaves the translational and orientational order in thisstructure but leads to a random distribution of p/3 rotations and hence to an "averaged" unit cell withtwo molecules. However the most relevant structural defects are not these intrinsic "misorientations"but some walls between the domains with different sequences of the above-mentioned two (nonideal) sublattices. Numerical estimates have been made for the anisotropic intermolecular potential, showing that the anisotropy is noticeably smaller for molecules in walls than in domains.